The Effect of Mindfulness-Based Psycho-Educational Program on Insight and Socio Occupational Functioning of Schizophrenic Patients (International Journal of Nursing Education, 2020)
Background: Schizophrenia causes many difficulties in the lives of patients because it is a chronic diseasethat reduces the mindfulness, causes disability, low insight, loss of social and vocational skills, and continueswith relapses. psychoeducation in either an individual or group format, on a fortnightly to monthly basis,should be offered to patients with schizophrenia as it is consistently effective in patients' awareness ofand insight into their schizophrenia and other functional outcomes. Mindfulness-based intervention helpspatients with schizophrenia relate differently to their psychotic experiences by opening their awareness andnon-judgmental acceptance and allow a more adaptive strategy of coping and control over those psychoticsymptoms to be used by patients with schizophrenia.Aim of the Study: The study aimed to assess the effect of mindfulness-based psychoeducation program oninsight and socio-occupational functioning of schizophrenic patients.Method: A quasi-experimental research design with a pretest-posttest is used to achieve the aim of the study.The study was conducted at The Psychiatric and Addiction Treatment Hospital in Meet-Khalaf that affiliatedto the Ministry of Health at Menoufia Governorate, Egypt. A convince sample of 58 schizophrenic patientsfrom inpatient of the above-mentioned setting was recruited for this study. The study sample was dividedinto two groups 30 patients in the case group and 28 patients in control. Three tools were used; Structuredinterview questionnaire, Beck Cognitive Insight Scale (BCIS) and Socio-Occupational Functioning Scale(SOFS).Results: The results of this study revealed that there a was a significant decrease of mean Socio occupationalfunctioning scale score in the study group after intervention than before (38.56±3.1 to be 28.23). Also, therewas a highly statistically significant difference found in the cognitive insight scale and its subscales scoreamong study groups pre and post-intervention.Conclusion: Mindfulness-based intervention have increased the cognitive insight and socio occupationalfunctioning of the patients in the study group.Recommendation: Mindfulness-based psych educational program should be implemented as a routine carefor all schizophrenic patients.